PENGARUH FIRM SIZE, LEVERAGE, SALES GROWTH DAN CASH FLOW TERHADAP CASH HOLDING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cahyani Murdijaningsih; Fajar Febrianti; Heru Cahyo (FEB UNWIKU PURWOKERTO, 2021)
The purpose of this research was to partially test the significance effect of firm size, leverage, sales growth and cash flow on cash holding in property and real estate companies listed at the Indonesia Stock Exchange (IDX) periode 2015-2019. The population in this study is property and real estate companies listed at the Indonesia Stock Exchange (IDX) which amounts to 77 companies. Purposive sampling used ad sampling technique, obtained 45 companies. The analytical tool used in this study is panel data regression with fixed effect model and with the help of E-views 10. The result of the research showed that firm size had negative and significant effect to cash holding. Leverage and cash flow had positive and significant effect to cash holding while sales growth didn’t have significant effect to cash holding